The Effect of Admission Blood Pressure on the Prognosis of Patients with Intracerebral Hemorrhage That Occurred during Treatment with Aspirin, Warfarin, or No Drugs - ASİL, TALIP; Balci, Kemal; Utku, Ufuk; Asil, TALİP; Celik, Yahya; Tekinaslan, Ilkay; Ir, Nasif; Unlu, Ercument (My University, 2012)
Background. Hypertension is the most important modifiable risk factor for intracerebral hemorrhage (ICH), but blood pressure (BP) management during the acute phase of ICH is still controversial. Approximately one-fourth of ICHs occur during treatment with warfarin or aspirin. Aim. This study was designed to determine the effect of admission BP on the early prognosis of ICH patients by dividing them into three groups (warfarin, aspirin, and no drugs). Methods. Three hundred and sixty-nine patients with supratentorial ICH were divided into three groups according to medication. Each group was evaluated in terms of prognosis and the risk for mortality based on the modified Rankin Scale (mRS) score at discharge (good prognosis: mRS 3). The effect of admission BP on prognosis was evaluated for each group. Results. The inhospital mortality rate was 72% for ICH patients treated with warfarin, 41.6% for ICH patients treated with aspirin, and 35% for ICH patients treated with no drugs. Admission mean arterial blood pressure (MABP) values were higher in patients with poor prognosis compared with patients with good prognosis for the aspirin (P = .002) and no-drug (P = .001) groups, but not in the warfarin (P = .067) group. Conclusion. A high MABP at admission was found to be an independent predictor of poor prognosis for ICH patients treated with aspirin or with no drugs, but not for ICH patients treated with warfarin.